Application of calcium-to-phosphorus (Ca/P) ratio in the diagnosis of pseudohypoparathyroidism: another piece in the puzzle of diagnosis of Ca-P metabolism disorders - De Vincentis, Sara; Del Sindaco, Giulia; Pagnano, Angela; Brigante, Giulia; Moretti, Antonio; Zirilli, Lucia; Rochira, Vincenzo; Simoni, Manuela; Mantovani, Giovanna; Madeo, Bruno (Frontiers in Endocrinology, 2023)
Objective The serum calcium (Ca)–to–phosphorus (P) ratio has been proposed to identify patients with primary hyperparathyroidism and chronic hypoparathyroidism (HPT), but it has never been tested in pseudohypoparathyroidism (PHP). The aim of this study was to test the performance of Ca/P ratio in PHP diagnosis compared with that in healthy subjects and patients with HPT for differential diagnosis. Design A retrospective, cross-sectional, and observational study was carried out. Methods Serum Ca, P, creatinine, parathyroid hormone (PTH), and albumin were collected. Ca and P were expressed in mmol/L. Ca/P diagnostic performance was evaluated by receiver operating characteristic curve, sensitivity, specificity, and accuracy. Results A total of 60 patients with PHP, 60 patients with HPT, and 120 controls were enrolled. The Ca/P ratio was lower in patients with PHP and HPT than that in controls (p < 0.0001). The cutoff of 1.78 (2.32 if Ca and P measured in mg/dL) for Ca/P ratio could identify patients with PHP and HPT among the entire cohort (sensitivity and specificity of 76%). No valid cutoff of Ca/P was found to distinguish patients with PHP from patients with HPT; in this case, PTH above 53.0 ng/dL identified patients with PHP (sensitivity and specificity of 100%). The index (Ca/P × PTH) above 116 ng/L recognized patients with PHP from controls (sensitivity of 84.7% and specificity of 87.4%), whereas (Ca/P × PTH) below 34 ng/L recognized patients with HPT from controls (sensitivity of 88.9% and specificity of 90.8%). Conclusions The Ca/P ratio below 1.78 (2.32 CU) is highly accurate to identify patients with PHP and HPT, although it is not reliable to differentiate these two conditions. The index (Ca/P × PTH) is excellent to specifically recognize PHP or HPT from healthy subjects.